2019
DOI: 10.1111/gtc.12731
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell study of neural stem cells derived from human iPSCs reveals distinct progenitor populations with neurogenic and gliogenic potential

Abstract: We used single‐cell RNA sequencing (seq) on several human induced pluripotent stem (iPS) cell‐derived neural stem cell (NSC) lines and one fetal brain‐derived NSC line to study inherent cell type heterogeneity at proliferating neural stem cell stage and uncovered predisposed presence of neurogenic and gliogenic progenitors. We observed heterogeneity in neurogenic progenitors that differed between the iPS cell‐derived NSC lines and the fetal‐derived NSC line, and we also observed differences in spontaneous diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 29 publications
4
37
0
Order By: Relevance
“…NES C9 and C7 were biased towards neuronal commitment, while NES AF22 generated a mixture of glial and neuronal populations. Our data corroborate with findings from other studies; specifically, NES AF22 has been shown to produce a mixture of glial and neuronal population upon growth factor withdrawal(Lam, Sanosaka, et al ., 2019) while NES C7 mainly generated neurons(Lam, Moslem, et al ., 2019). Adhering to that paradigm, NES AF22 should have the greatest potential for astrocyte differentiation (compared to NES C7 and NES C9), but strikingly NES AF22 underperformed compared to NES C9 and NES C7.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…NES C9 and C7 were biased towards neuronal commitment, while NES AF22 generated a mixture of glial and neuronal populations. Our data corroborate with findings from other studies; specifically, NES AF22 has been shown to produce a mixture of glial and neuronal population upon growth factor withdrawal(Lam, Sanosaka, et al ., 2019) while NES C7 mainly generated neurons(Lam, Moslem, et al ., 2019). Adhering to that paradigm, NES AF22 should have the greatest potential for astrocyte differentiation (compared to NES C7 and NES C9), but strikingly NES AF22 underperformed compared to NES C9 and NES C7.…”
Section: Discussionsupporting
confidence: 93%
“…Albeit having a different regional identity, all hiAstrocytes stained positive for the canonical astrocytic markers, S100B, AQP4, ALDH1L1 and CD44. Interestingly, the generated cells are GFAP + which was not observed in our previous protocol to generate astrocytes from long-term proliferating NES(Lundin et al ., 2018, 2020; Lam, Sanosaka, et al ., 2019). NES (all lines) did not stain for any of these markers but were positive for VIMENTIN (Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…These additional factors help increase the abundance of GFAP + cells but may simultaneously induce aspects of astrocyte reactivity ( Sofroniew, 2020 ). Once directed toward an astroglial cell fate, some protocols allow time to mature astrocyte progenitors ( Lam et al, 2019b ) while others direct astrocyte maturation with additional exogenous molecules ( Krencik and Zhang, 2011 ). The former likely produces more bona fide astrocyte-like cells but at the consequence of longer protocols (up to 180 + days).…”
Section: D Glial Stem Cell Modelsmentioning
confidence: 99%
“…For example, certain polymorphisms in the dyslexia candidate genes DYX1C1, DCDC2, and KIAA0319 correlate with white matter density in the brain of children [59]. Recently, protocols to differentiate NES cells into the [23,60]. We further focused our analysis on a group of DCGs highly replicated in genetic studies and previously linked to neuronal development and cilia.…”
Section: Discussionmentioning
confidence: 99%